Stressor Psikologis Pada Ibu dengan Kejadian Bayi Berat Lahir Rendah - Gustika Anggraini (LPPM STIKES Al-Ma'arif Baturaja, 2020)
Objective to find out the relationship between psychological stressors in mothers and the incidence of low birth weight babies in Puskesmas Prabumulih Timur, Prabumulih City in 2019. This study uses an Analytical Survey using a Cross-Sectional approach. The population of this study was maternity mothers who had babies with an LBW incidence of 57 respondents. The number of samples in this study was 57 respondents. Bivariate analysis shows that maternal age has a significant relationship with LBW events (p-value 0,000), occupational mothers have a significant relationship with LBW events (p-value 0,000) and family income has a significant relationship with LBW events (p-value 0.001). The conclusion that there is a relationship between psychological stressors in mothers with the incidence of low birth weight babies in the Prabumulih Puskesmas in Prabumulih city in 2019.